(Breaking) The Iron Triangle of Evaluation. (January 2015) - Reynolds, Martin
Abstract Ideas from complexity science and systems thinking are demonstrably helpful in a shift from exploring (systematic) linear net effects of an intervention towards exploring wider (systemic) effects occurring elsewhere. But where these ideas of 'impact' are coupled with a narrow use of the contingency approach, some less helpful 'triangulated' relationships might be evident. These relationships might be regarded in terms of an 'iron triangle', a metaphor used frequently to exemplify pernicious relations of power. The most notable expression of the iron triangle is the 'military–industrial complex'. This article briefly outlines generic features of the iron triangle in terms of 'systemic triangulation' – an idea linking three core systems concepts of interrelationships, perspectives and boundaries. Drawing on a tradition of systems thinking in practice, an associated systemic triangulator is introduced as both a diagnostic and planning heuristic; a device for not only diagnosing symptoms of an evaluation–industrial complex but for prompting ideas towards a more benign evaluation–adaptive complex for impact evaluation.